Evaluating the recycling potential of ashes discharged from waste incineration facilities and its dependency on pretreatment efficiency in Korea - Kyu Choi, Myung (Waste management (New York, N.Y.), 2023)
Copyright © 2023 Elsevier Ltd. All rights reserved.